MEMBANGUN LITERASI SAINS SISWA SD MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA MATERI “INI KHAS DAERAHKU - Hamidah Yuliyana; Hani Handayani; Asep Nurhuda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the use of the Make A Match learning model to improve science literacy in fourth grade elementary students on the topic "Ini Khas Daerahku". Science literacy among Indonesian elementary students remains low. Students struggle to explain scientific phenomena, evaluate investigations, and interpret data. This study uses a quantitative approach with a quasi-experimental nonequivalent control group design. The sample consists of 56 fourth grade students from SDN 1 Cikopo Purwakarta, divided into 28 students in the experimental group and 28 students in the control group. The experimental group received instruction using the Make A Match model, while the control group received conventional instruction. Data were collected through a 20-item multiple-choice science literacy test. The data were analyzed using the Shapiro-Wilk normality test, homogeneity test, mean difference test, and Cohen's d effect size test with IBM SPSS Statistics. The results show that the experimental group achieved a posttest mean of 88.84 and an N-Gain of 82.01%. The control group achieved a posttest mean of 64.11 and an N-Gain of 34.95%. The Independent Sample T-Test on N-Gain shows a significance value of 0.000 (p < 0.05). The Cohen's d value of 7.06 indicates a very large effect. These results show that the Make A Match learning model improves student science literacy significantly compared to conventional instruction. Teachers can use this model to develop science literacy skills in elementary students, particularly for materials related to regional characteristics and potential.